Clinical analysis of special types of tracheobronchial foreign bodies in children - Cai, Hao; Gao, Jinjian (Frontiers in Pediatrics, 2024)
To explore the clinical diagnosis and treatment of special types of tracheobronchial foreign bodies in children and provide a reference for clinicians to formulate treatment plans. Methods: Clinical data of 29 children with special types of tracheobronchial foreign bodies who were treated at The Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University between June 2017 and June 2022 were collected and analyzed, and their diagnosis and treatment processes were reviewed.Results: All 29 special types of foreign bodies were successfully removed using rigid bronchoscopy under general anesthesia, with no surgical complications.For the treatment of special types of tracheobronchial foreign bodies, clinicians should make detailed surgical plans and select appropriate instruments according to different conditions to improve the surgical success rate and reduce the occurrence of complications.